Выразите a через b если a^2-3ab+2b^2=0 и решите уравнение (3x-2)^2-3(3x-2)(7x-5)+2(7x-5)^2=0

1

Ответы и объяснения

Лучший Ответ!
  • oksanashn
  • почетный грамотей
2014-04-14T22:32:18+04:00
a_{1,2}=\frac{3b+-\sqrt{9b^{2}-4*2b^{2}}}{2}= \frac{3b+- \sqrt{b^{2}}}{2}= \frac{3b+- b}{2}
a_{1}=\frac{3b+b}{2}=\frac{4b}{2}=2b
a_{2}=\frac{3b-b}{2}=\frac{2b}{2}=b

В приведенном уравнении
a=3x-2
b=7x-5

Для a1=2b:
3x-2=2(7x-5)
3x-2=14x-10
14x-3x=10-2
11x=8
 x=\frac{8}{11}

Для a2=b:
3x-2=7x-5
7x-3x=5-2
4x=3
 x=\frac{3}{4}